Remote control desktop system / Muhammad Akmal Idlan Hissamuddin and Ros Syamsul Hamid - Hissamuddin, Muhammad Akmal Idlan; Hamid, Ros Syamsul (College of Computing, Informatics and Media, UiTM Perlis, 2023)
A remote-control desktop system allows a user to access and control a computer remotely over a network connection. This can be done through various remote desktop software and protocols, such as Remote Desktop Protocol (RDP) or Virtual Network Computing (VNC). These systems are often used in scenarios where a user needs to access a computer remotely, such as for remote work or remote technical support. The system allows the user to access the desktop, files, and applications of the remote computer as if they were physically sitting in front of it. This can provide flexibility and convenience for users, as well as enabling remote collaboration and support. The security and performance of remote-control desktop systems can be a concern and requires proper configuration and maintenance. Therefore, the aim of this research is to design and develop a remote-control desktop system that can control in any device. The software development life cycle (SDLC) with waterfall model has been chosen as the methodology for this study. this model consists of five phases including analysis, design, implementation, testing and documentation. this research has achieved the objectives which are to design, develop and evaluate a remote-control desktop system with NodeJS and electrons.